ADMINISTRATIVE DATA SYSTEMS DESIGN COMPUTERIZED RESIDENTKAYUMANIS IV BARU RT004/04 USING MICROSOFT ACCESS 2000 - Alen Wulan Sari; Yuce Yulina, SKom, MM (Jurnal Sistem Informasi, 2002)
With existence of computerized system of service is expected to be faster in dealing with administrative access to data resident RT 004/04 KayumanisIV Baruresidents as well as search data, blueprints of the house, compared with the manual method.In order for the data administration of new citizens IV RT 004/04 Kayumanisand running well, then the required information and reports on concrete, as well as monthly reports, a list of residents.This can be done by the computerized data of new residents KayumanisIV RT 004/04 which has been previously accessed, can be implemented quickly with rock media via computer software Microsoft Access.